The coastal community perception on the socio-economic impacts of agro-tourism activities in coastal villages in Malaysia - Mohamed Shaffril, Hayrol Azril; Hamzah, Azimi; Md. Yassin, Sulaiman; Abu Samah, Bahaman; Alby, Jeffrey Lawrence D'Silva; Tiraieyari, Neda; Muhammad, Mahazan (Routledge, 2015)
This paper is concerned with the socio-economic impacts of agro-tourism activities in coastal villages listed as Desa Wawasan Nelayan (DWN) in Malaysia. The paper discussed the impacts of the two major components of socio-economics dynamics, namely social and economic activities. This account highlights a number of discussions with specific reference to DWN in Malaysia. It identifies the similarities and differences with regard to socio-economic impact, and it is expected that these points will be of practical use for other agro-tourism areas around the globe, and help to increase interest in agro-tourism activities.